Hospital Management System: All-in-One Guide - ., Abhishek; ., Shashank; ., Nipun (Journal of Advanced Research in Information Technology, Systems and Management; Vol 7 No 1 (2023): Journal of Advanced Research in Information Technology, Systems and Management, 2023)
The Hospital Management System is developed for the hospital to simplify the whole hospital’s tasks. It facilitates manipulating patient’s information, doctor’s information and many more tasks like appointments, billing etc. of hospital. The purpose of making this project is to simplify the work for a hospital. This project will help hospital to maintain the records of the patients, doctors, appointments etc. The admin can easily manipulate anything. With the help of this project, the burden of paperwork and updating records on the registers will be reduced as we have records of those patients who have been admitted in the hospital and for how much time they stayed and for which they have been admitted along with the type of treatment given to them in the hospital. We have mainly one panel in our program which is only for the receptionist as only receptionist makes bills or fills appointment. In this panel, the receptionist has his/her login id and after that he/ she can enter the main window of our program and then he/she can easily enter anything like he/she can fill, view, search, delete records of patient and doctors, bills, appointments. Hospital management system is a desktop application which would be built by using python and its libraries for database we are going to use MySQL and for to locally host it we are going to use Xampp which. All these are open sources and free to use so there would be no investment for the development